Betacarotene micellarization during in vitro digestion and uptake by caco2 cells is directly proportional to betacarotene content in different genotypes of cassava - Thakkar, S.K.; Maziya-Dixon, B.B.; Dixon, A.; Failla, M.L. (2007)
Cassava, a staple food in sub-Saharan Africa, does not provide adequate amounts of pro-vitamin A (VA) carotenoids and has been targeted for biofortification (i.e. selectively breeding cultivars of increased nutrient density with agroeconomically acceptable characteristics). However, the accessibility of pro-VA carotenoids for absorption in different cultivars of cassava remains unknown. Here, we used the coupled in vitro digestion/Caco-2 cell uptake model to screen the relative accessibility of beta-carotene (betaC) in 10 cultivars of cassava with varying concentrations of betaC. After cooking (boiled for 30 min), the betaC concentration in tubers from different cultivars ranged from less than detectable to 6.9 microg betaC/g cassava. Samples were subjected to simulated oral, gastric, and small intestinal digestion to determine stability and micellarization of betaC. All-trans betaC, 9-cis betaC, and 13-cis betaC were the most abundant carotenoids in cooked cassava and recoveries after digestion exceeded 70%. Efficiency of micellarization of total betaC was 30 +/- 2% for various cultivars with no significant difference in isomers and linearly proportional to concentration in cooked cassava (r = 0.87; P < 0.001). Accumulation of all-trans betaC by Caco-2 cells incubated with the diluted micelle fraction for 4 h was proportional (R(2) = 0.99; P < 0.001) to the quantity present in micelles. These results suggest that all-trans betaC content appears to provide the key selection marker for breeding cassava to improve VA status and that the more complicated screening procedure using in vitro digestion coupled to cell uptake does not provide additional information on potential bioavailability.